2018
DOI: 10.1007/s40263-018-0490-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Patients with Major Depressive Disorder: Prevalence, Burden and Pharmacological Approaches to Management

Abstract: Fatigue is a frequently reported symptom in major depressive disorder, occurring in over 90% of patients. Clinical presentations of fatigue within major depressive disorder encompass overlapping physical, cognitive and emotional aspects. While this review addresses the epidemiology, burden, functional impact and management of fatigue in major depressive disorder, the main focus is on available pharmacotherapy options and their comparative efficacies. Our review of the effects of pharmacological treatments on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…It is characterized by depressed mood, apathy, anhedonia, sleep disturbances, appetite or weight changes, psychomotor retardation [67] or agitation, cognitive impairment, thoughts of guilt, and recurrent thoughts about death or suicide [68]. This mental disorder, strongly associated with fatigue, loss of productivity, and increased mortality, represents an economic burden for public health [69].…”
Section: Depressionmentioning
confidence: 99%
“…It is characterized by depressed mood, apathy, anhedonia, sleep disturbances, appetite or weight changes, psychomotor retardation [67] or agitation, cognitive impairment, thoughts of guilt, and recurrent thoughts about death or suicide [68]. This mental disorder, strongly associated with fatigue, loss of productivity, and increased mortality, represents an economic burden for public health [69].…”
Section: Depressionmentioning
confidence: 99%
“…Fatigue is common in depressed patients, particularly in those with comorbid somatic symptoms. Previous studies have found that most patients with major depression complain of fatigue (Ghanean et al, 2018), which may be partly due to common underlying genetic factors (Cor eld et al, 2016). In addition, fatigue could be induced by antidepressant medications (Marin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is common in depressed patients, particularly in those with comorbid somatic symptoms. Previous studies have found that many depressed patients complain of fatigue (Conradi et al, 2011;Ghanean et al, 2018;McIntyre et al, 2002), an effect that may be partly due to common underlying genetic factors (Cor eld et al, 2016). In addition, fatigue could be induced by antidepressant medications (Marin & Menza, 2004).…”
Section: Discussionmentioning
confidence: 99%